Severe asthma and asthma-COPD overlap: a double agent or identical twins? - Xia, Yang; Cao, Yuan; Xia, Lexin; Li, Wen; Shen, Huahao (Journal of Thoracic Disease, 2017)
Since the joint project of asthma-chronic obstructive pulmonary disease (COPD) overlap syndrome first released by the Global Initiative for Asthma (GINA) and Global Initiative for Chronic Obstructive Lung Disease (GOLD), numerous debates have been triggered. However, the term asthma-chronic obstructive pulmonary disease overlap syndrome (ACOS) remained controversial. Furthermore, ACOS is replaced by asthma-COPD overlap (ACO) and the concept of a syndrome is no longer advised in GINA 2017. In 1961, “Dutch hypothesis” promulgated that the various forms of airway obstruction, including asthma, chronic bronchitis, and emphysema, should be considered as different expressions of one disease entity (1). Conversely, the opposing “British hypothesis” cited asthma and COPD as distinct clinical entities, with different inflammatory cells and mediators, in return, different responses to therapy (2).